Evolution behavior of oxide inclusions in Si-Mn deoxidized steel during billet heating process - Nie X.-L.; Xu Q.; Xie X.; Li J.-L. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In order to minimize the impact of oxide inclusions on the quality of Si-Mn deoxidized steel, the effects of heat treatment temperature and holding time on the inclusion composition and morphology were studied. LX82A billets were heated isothermally at 1000, 1100, and 1200°C for 8, 10, and 12 hours, respectively. The experimental results show that as the heat treatment temperature increases, calcium treatment and the reduction of the w(Al2O3 + MgO) / w(SiO2 + MnO) ratio enhance the deformability of the oxide inclusions. This causes a gradual transition in inclusion shape from oval to round. At 1200°C, the oxide inclusions are predominantly regular and round. With increasing heat treatment temperature and holding time, the oxide inclusions in Si-Mn deoxidized steel shift from the CaO-SiO2-Al2O3 system to the MnO-SiO2-Al2O3 system. At a constant temperature, the highest inclusion transformation rate and the most uniform composition occur at a 10-hour holding time. At 1200°C, an alternative calcium treatment and the steel matrix-inclusion interface reaction increase the MnO content at the interface, reducing the manganese content in the steel and forming a Mn-depleted zone. This decreases austenite stability, enhances ferrite nucleation, and improves the steel quality and performance. Therefore, controlling the heat treatment temperature around 1200°C is crucial.